Assessing enabling environment, institutional capacity and pathways to transformative gender responsive budgeting in Bangladesh - Joshi, Deepa; Khan, Md. Tarikul Islam; Rahman, Shadlee; Ramakrishnan, Harini; Mannan, Fouzia; Sarker, Mou Rani (CGIAR Scaling for Impact Program, 2025)
Gender Responsive Budgeting (GRB) is an international planning instrument developed to enable national governments to plan, implement and track the outcomes of gender equitable budgets. Without a robust and strategic gender budgeting system, it is not possible to translate policy prescriptions to gender equality. Currently, 100 countries have initiated efforts on gender-responsive budgeting to address the historical underinvestment in women and girls. However, data from over 105 countries shows that of this total, only 27 have comprehensive systems to track gender equality allocations in their financial budgets.